Sick building syndrome, multiple chemical sensitivity, and related factors: A cross-sectional analysis from the Japan Environment and Children’s Study - Yasuaki Saijo; Eiji Yoshioka; Yukihiro Sato; Hiroyuki Shiotsuki; Kentaro Nakanishi; Yasuhito Kato; Ken Nagaya; Satoru Takahashi; Yoshsiya Ito; Atsuko Ikeda; Hiroyoshi Iwata; Takeshi Yamaguchi; et al. (PLoS ONE, 2025)
Sick building syndrome (SBS) is caused by having unhealthy indoor environments. Multiple chemical sensitivity (MCS) is a chronic condition that is potentially triggered by low-level chemical exposure. Demographic factors, lifestyle factors, and comorbidities have been reported as potential risk factors of both conditions; however, studies on these factors involving large populations in Japan are limited. The aim of this study was to investigate whether demographics, lifestyle, and comorbidities were associated with MCS and SBS in a large Japanese population, and whether autistic traits (Japanese version of the Autism-Spectrum Quotient Short Form, AQ-10-J), psychological distress (Japanese version of the Kessler 6-Item Psychological Distress Scale, K6), and serum total and allergen-specific immunoglobulin E (IgE) levels were related to the outcomes. The participants included 92,387 pregnant women and 48,451 partners. The outcomes were self-reported physician-diagnosed SBS, MCS, and SBS and/or MCS (combined outcome [CO]). Age-adjusted odds ratios (ORs) of total and antigen-specific IgE levels, demographic factors, and lifestyle factors were determined. The proportions of pregnant women with SBS, MCS, and CO were 307 (0.33%), 128 (0.14%), and 415 (0.45%), respectively, while those of their partners were 85 (0.18%), 30 (0.06%), and 112 (0.23%), respectively. Allergic diseases, psychiatric diseases, migraine, and higher psychological distress were associated with significantly higher ORs for SBS, MCS, and CO. Among pregnant women, autoimmune diseases, cancer, kidney diseases, higher physical activity, autistic traits, and total and specific IgE levels were associated with significantly higher ORs for SBS, MCS, and CO. Clinicians should consider common comorbid disorders when treating patients with SBS and MCS, and their protective and deteriorating lifestyles and demographic factors should be clarified.